Planning Mechanisms in Community Development Efforts in Nagari Pasar Muara Labuh, Sungai Pagu District, South Solok Regency - Takdir, M.; Bakhtiar, Riswanto (The Future of Education Journal, 2026)
In carrying out development in Pasar Muara Labuh Village, especially regarding education, health, youth and sports programs, law, order, security and village development planning, has been carried out by the local community through the Nagari Medium-Term Development Plan (RPJMN) which is made as a reference in the implementation of development determined by the Nagari Government together with Bamus Nagari and agreed upon with community elements as the direction of government administration through the Nagari Development Planning Meeting (Musrenbang) which is the main vehicle for public consultation for annual development planning. The preparation of the RPJM is carried out systematically, directed, integrated, gradual and sustainable in accordance with the main tasks and functions for the coming year. The research method used is descriptive qualitative. Data collection techniques are carried out through document searches in the form of literature studies and observations, in-depth interviews with informants. Collected data are analyzed using descriptive qualitative analysis. A persistent challenge in the field is the lack of qualified educational staff. The implementation of the Community-Based Learning (KBK) system remains suboptimal, as evidenced by the lack of learning completion from primary to secondary levels. Health facilities and infrastructure in Pasar Muara Labuh Village remain inadequate, impacting the provision of health services. Sectoral egos and a lack of unity among youth persist at the village level. The high percentage of the population in Pasar Muara Labuh Village remains high. Government programs to alleviate poverty are still suboptimal. To address the issue of maintaining development outcomes, the Pasar Muara Labuh Village strives to support active, creative, effective, and enjoyable learning and guidance, ensuring that each student develops optimally according to their potential. The village government acts as a coordinator in determining all strategic policies for implementing development and health. It is recommended that Pasar Muara Labuh Village continue to employ a mentoring approach, motivating the community to actively participate in maintaining existing development outcomes. This is crucial for attracting government participation and achieving greater development in the following year.